2013
DOI: 10.1002/anie.201208025
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Cross‐Coupling of Mesylates Catalyzed by Copper/Palladium Systems with Customized Imidazolyl Phosphine Ligands

Abstract: Decarboxylative cross-coupling reactions have recently emerged as a powerful methodology for the regioselective construction of CÀC and CÀheteroatom bonds. [1] Their key advantage over traditional cross-coupling reactions is that they draw on stable and readily available carboxylate salts as sources of carbon nucleophiles rather than expensive and sensitive organometallic reagents. In the last decade, a rapidly growing number of decarboxylative reactions have been discovered including decarboxylative Heck rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(29 citation statements)
references
References 94 publications
2
27
0
Order By: Relevance
“…Notably, the 3-(p-tolyl)propiolic acid 1b and meta-substituted counterpart 1c afforded similar yields of 70% and 61%, respectively, but sterically demanding 3-(o-tolyl)propiolic acid only gave a very low yield of 9%, illustrating that this coupling reaction is sensitive to steric hindrance (entries 2 and 3). Interestingly, fluoro group substituted substrates such as 1f, 1g and 1h could well be coupled with diethyl hydrazinylphosphonate 2a, affording the desired products in moderate yields ( Table 2, [10][11][12]. To gain more insight into the substrate scope of the reaction, in addition to 1a, the alkynylation of diisopropyl hydrazinylphosphonate (1b) and P,P-diphenylphosphinic hydrazide were also detected.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Notably, the 3-(p-tolyl)propiolic acid 1b and meta-substituted counterpart 1c afforded similar yields of 70% and 61%, respectively, but sterically demanding 3-(o-tolyl)propiolic acid only gave a very low yield of 9%, illustrating that this coupling reaction is sensitive to steric hindrance (entries 2 and 3). Interestingly, fluoro group substituted substrates such as 1f, 1g and 1h could well be coupled with diethyl hydrazinylphosphonate 2a, affording the desired products in moderate yields ( Table 2, [10][11][12]. To gain more insight into the substrate scope of the reaction, in addition to 1a, the alkynylation of diisopropyl hydrazinylphosphonate (1b) and P,P-diphenylphosphinic hydrazide were also detected.…”
Section: Resultsmentioning
confidence: 96%
“…The transformation could not proceed without the participation of CuSO 4 , revealing that CuSO 4 catalyst was essential to achieve a high yield of product 2a. To advance the process further, the effect of solvents was also investigated, such as CH 3 CN, 1, 4-dioxane and toluene, however, no desired product was observed (entries [10][11][12]. Subsequent survey on the role of oxidants disclosed H 2 O 2 or tert-butyl hydroperoxide (TBHP) could not promote this reaction (entries [13][14].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[9] More recently, the Wu and Stoltz research groups achieved the bimetallic Pd 0 /Cu I -catalyzed decarboxylative coupling of unsubstituted 2-azynylcarboxylic acids by using only aryl bromides as coupling partners (Scheme 1, [Eq. Two mechanisms have been considered; 1) the conventional bimetallic-catalyzed decarboxylative cross-coupling reaction (Figure 1, cycles A and C) [2,15,16] and 2) the direct CÀH arylation of the protodemetalated N-oxide substrate (Figure 1, cycles B and C). [10] Recent calculations and studies of this dual catalysis (Pd/Cu or Pd/Ag) revealed that the decarboxylative metalation likely proceeds by means of an ipso-interaction of the metal (Cu I or Ag I ) on the carboxylate function, and could be facilitated by the electron-withdrawing effect of a heteroatom at the orthoposition.…”
mentioning
confidence: 99%
“…[10] Recent calculations and studies of this dual catalysis (Pd/Cu or Pd/Ag) revealed that the decarboxylative metalation likely proceeds by means of an ipso-interaction of the metal (Cu I or Ag I ) on the carboxylate function, and could be facilitated by the electron-withdrawing effect of a heteroatom at the orthoposition. Two mechanisms have been considered; 1) the conventional bimetallic-catalyzed decarboxylative cross-coupling reaction (Figure 1, cycles A and C) [2,15,16] and 2) the direct CÀH arylation of the protodemetalated N-oxide substrate (Figure 1, cycles B and C). Moreover, N-oxidation of azines is one of the most employed activation methods to introduce various substituents at the C2 position.…”
mentioning
confidence: 99%